Understanding Neighbourhoods as Multifaith Spaces - Prideaux, Melanie (Religions, 2019)
This paper asked whether it is possible to understand neighbourhoods as multifaith spaces' and whether doing so helps us think differently about neighbourhoods or about multifaith spaces. By referring to the English context, this paper explored the significance of the local and the demotic in the experience of religious diversity, the construction of space as multifaith', and the practice and experience of interfaith dialogue. It concluded that thinking of neighbourhoods as multifaith spaces both challenges how multifaith spaces are identified and articulated and deepens the discussion of neighbourhoods as key to the experience of living with religious diversity.